Estudo das propriedades tribômecânicas de compósitos de politetrafluoretileno com quasicristal - Silva, Aline Karla Barbosa da (2018)
The development of new materials that may contribute to the improvement of tribological systems such as reduced friction and decreased wear has been of interest to researchers worldwide. The use of PTFE as a high performance thermoplastic has already been established in the market due to its excellent surface characteristics, low coefficient of friction, and high lubrificity, associated to the high performance under impact. Among the disadvantages in the use of this material is the low wear resistance as well as limited mechanical resistance. The objective of this work was the development of PTFE composite with powder loading of quasicrystalline alloys in order to obtain a material with excellent surface characteristics, due to the characteristics of the matrix as well as the metallic powder, associated with high wear resistance and mechanical properties. quasicrystalline reinforcement. The quasicrystalline alloys were obtained by melting the precursor elements; heat treated and comminuted in high energy planetary mills. The composites were developed by hot sintering of PTFE with added powder loading of icosaedral quasicrystalline AlCuFe alloys. To the PTFE matrix were added metallic reinforcement powders in variable volumetric fractions (1% -20% Vol.). The tests of Pin on disk, Wettability, Roughness, Shore D Hardness, Ultramicrodureza and Morphological analysis were carried out. Obtaining as positive results in relation to the wear where the polymer matrix had an increase of its resistance to wear with the increase of the loads of quasicristais. The hardness had a significant increase where the composition of 20% obtained a hardness of 51.4 Shore D, attesting the feasibility in the development of composite PTFE / QC, of high technological performance.